Indoor positioning system on identification of neurodegenerative disease: A comparative study of BLE versus RFID - Jayasvasti, Subhawat; Isarakorn, Don (My University, 2019)
This paper introduces the feasibility examination of indoor positioning system using the Bluetooth low energy (BLE) and the radio-frequency identification (RFID) devices to further apply in the diagnosis of neurodegenerative disease leading an unusual human body motion. Experimentally, a BLE module and a RFID tag are simulated to be the wearable devices mounted to human body, moving with common body motions. Their movements affecting on position tracking efficiency are investigated through smartphone and ultra-high frequency RFID reader, respectively. The results show that a BLE device presents the best position sensing ability.
Keywords: Bluetooth low energy (BLE); position tracking for identification of neurodegenerative disease; radio frequency identification (RFID)